Rekonstruksi Strategi Pembelajaran PAI melalui Sintesis Akulturasi Islam Nusantara dan Etika Ekologis - Tazkiyatun Nafiah. P; Dika Tripitasari; Ahdar Ahdar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to formulate an integrated Islamic Religious Education (PAI) learning strategy that synthesizes the acculturation of Islam Nusantara and ecological ethics as a response to the fragmented character of conventional PAI learning which has not yet optimally integrated local cultural values and ecological awareness. This research employs a qualitative library research method with a systematic literature review approach, analyzing 28 primary sources selected from 67 identified literature published between 2019 and 2025. Data were analyzed using Braun and Clarke's thematic analysis through six stages: familiarization, initial coding, theme searching, theme reviewing, theme defining, and report writing. The findings reveal that Islam Nusantara contains three relevant pedagogical principles cultural humility (tawadu' budaya), cosmological inclusivity, and peaceful transformation while Islamic teachings hold rich ecotheological dimensions through the concepts of ecological tauhid, khalifah fi al-ardh, amanah, and rahmatan lil 'alamin. Based on this synthesis, four integrated learning strategies are formulated: Contextual-Cultural Learning, Eco-Thematic Quranic Interpretation, Community-Based Ecological Projects, and Ecological Spiritual Reflection. This study proposes a new conceptual framework termed